Novel insight into the composition of human single-stranded DNA-binding protein 1 (hSSB1)-containing protein complexes. Issue 1 (December 2016) - Ashton, Nicholas; Loo, Dorothy; Paquet, Nicolas; O'Byrne, Kenneth; Richard, Derek
Abstract Background Single-stranded DNA-binding proteins are essential cellular components required for the protection, metabolism and processing of single-stranded DNA. Human single-stranded DNA-binding protein 1 (hSSB1) is one such protein, with described roles in genome stability maintenance and transcriptional regulation. As yet, however, the mechanisms through which hSSB1 functions and the binding partners with which it interacts remain poorly understood. Results In this work, hSSB1 was immunoprecipitated from cell lysate samples that had been enriched for non-soluble nuclear proteins and those associating with hSSB1 identified by mass spectrometry. In doing so, 334 potential hSSB1-associating proteins were identified, with known roles in a range of distinct biological processes. Unexpectedly, whilst hSSB1 has largely been studied in a genome stability context, few other DNA repair or replication proteins were detected. By contrast, a large number of proteins were identified with roles in mRNA metabolism, reflecting a currently emerging area of hSSB1 study. In addition, numerous proteins were detected that comprise various chromatin-remodelling complexes. Conclusions These findings provide new insight into the binding partners of hSSB1 and will likely function as a platform for future research.